„Trachinki” Sofoklesa i „Agamemnon” Ajschylosa – zależność czy zbieżność struktur? - Chodkowski, Robert R. (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The author of the article draws our attention to the similarities between the two plays, i.e. Sophocles’ Trachiniae and Aeschylus’ Agamemnon. These similarities apply to the plot structure, the structure of characters, and the time and space dimensions of drama. In author’s opinion, the observed similarities and convergences prove that The Trachiniae appeared in the period when Sophocles was still under his predecessor’s infuence and the drama belongs to the earliest of his tragedies that survived.
Sophocles’ Trachiniae and Aeschylus Agamemnon: interrelation or convergence of structures?
Keywords: Greek tragedy; The Trachiniae of Sophocles; Agamemnon of Aeschylus; Interrelation of tragedy structures